(untitled) (Cinéma & Cie. Film and Media Studies Journal, 2013)
This article returns to the experimental theory and practice of Third Cinema as developed in the late 1960s in parts of Latin America. It focuses on two of its aspects that have not been systematically researched: Third Cinema as conceptualizations and maps of global capitalism. In doing so this article takes up and reconfigures Fredric Jameson’s notion of “cognitive mapping” and introduce the theory concept-cognitive mapping. This latter theory aims to contribute new thoughts and perspectives to ongoing debates on aesthetic forms capable of a critical grasp of the mechanisms of advanced capitalism.